Diameter Zona Hambat Antibiotik Amoxicillin dan Tetracycline terhadap Escherichia coli - Helen Anjelina Simanjuntak; Herlina Simanjuntak; Siti Maimunah; Rahmiati Rahmiati; Toberni S Situmorang (Herbal Medicine Journal, 2022)
Antibiotics are drugs used for infections caused by bacteria. Amoxicillin and tertacycline are antibiotics used to inhibit the growth of Escherichia coli. Escherichia coli bacteria can cause urinary tract infections, diarrhea, gastroenteritis, pneumonia, septicemia, and meningitis. The purpose of this study was to determine the diameter of the inhibition zone of amoxicillin and tetracycline antibiotics in inhibiting Escherichia coli bacteria. Experimental research method with antibacterial activity test using paper disc diffusion method. The results showed that amoxicillin and tetracycline antibiotics had inhibition zone diameters of 18.4 mm and 35.76 mm, respectively, with strong and very strong categories. The conclusion of this study is that tetracycline antibiotics are better at inhibiting the growth of Escherichia coli bacteria than amoxicillin.